2016
DOI: 10.1080/10498850.2014.896063
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Whey Protein Isolate Coating Enriched with Thyme Essential Oils on Trout Quality at Refrigerated Storage (4 ± 2°C)

Abstract: The present study evaluated the effect of whey protein isolate (WPI) coating enriched with thyme essential oil (EO; 3, 5, and 7 %, v/v) on whole trout chemical and microbial quality during refrigerated storage at 4±2 o C. As a result of this study, the addition of thyme essential oil to WPI coatings enhanced quality significantly better than that of the control and WPI coating without thyme essential oil during refrigerated storage, and this effect increased with increase in the thyme EO concentration in WPI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…showed lower pH values as compared with control samples. Similar findings were reported by other researchers (Ahmad et al, 2012;Tokur et al, 2016;Zakipour Rahimabadi & Divband, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…showed lower pH values as compared with control samples. Similar findings were reported by other researchers (Ahmad et al, 2012;Tokur et al, 2016;Zakipour Rahimabadi & Divband, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Badr, Ahmed, and Elgamd (2014) observed that whey protein edible films incorporated with thyme, cinnamon, and cumin essential oils treatment significantly reduced the growth of total volatile count in fresh beef. Tokur et al (2016) stated that WPI coating enriched with thyme essential oils in the preservation of rainbow trout fillets retarded the growth of aerobic microorganisms during refrigeration storage (48C 6 28C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment also decreased the population of E. coli O157:H7 to less than 2 log cfu/g beginning at day 4 of storage. Tokur et al [ 116 ] coated whole trout with a whey protein coating containing thyme EO (TEO) held under refrigeration. The results of the study showed that an increase in the amount of TEO used resulted in an increase in the shelf life of the trout.…”
Section: Seafood Packaging Technologiesmentioning
confidence: 99%
“…Use of Mentha essential oil and whey protein coating showed more antibacterial effects on various bacteria, compared to that use of garlic and rosemary did (4). Antibacterial activity of whey protein coating and 5% Mentha essential oil was investigated in beef packaging (5) and traditional lighvan cheese (6) with the highest inhibitory effects on Escherichia coli, Pseudomonas and Listeria monocytogenes. Moreover, Mentha essential oil associated with chitosan coating was an effective antibacterial packaging system against E. coli, Staphylococcus aureus and L. monocytogenes in Iranian white cheese.…”
Section: Introductionmentioning
confidence: 99%